Fracture toughness and related characteristics of the cryogenic nickel steels - Pense, A. W.; Stout, R. D. (Nickel Institute, 1983)
This report is intended to summarize the available information published in the last 15 years about the mechanical properties of steels containing 2 1/4 to 9% Ni designed for low-temperature and cryogenic applications. Further, this information is evaluated critically to put a current view of the range of usefulness of these steels at the disposal of practitioners in the field.